A Brief Overview of Several Challenges in Finger Vascular Pattern Recognition - Normakristagaluh, Pesigrihastamadya (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
Finger vascular pattern recognition biometrics are gaining popularity because they are hard to duplicate and more convenient. However, the challenges addressed during this research are not well-known to the public. Therefore, this paper presents an overview of challenges in finger vein pattern recognition. The challenges described arise from three possible things, namely imaging devices, finger physiology, and the surrounding environment. An illustrative experiment for one of the challenges has been carried out by producing that overexposure illumination during the image acquisition process can cause loss of vein pattern images. In addition, the experiment results on one of the finger images with different skin colors (light and dark) are shown in the histogram of the two images, where there is a slight difference in the graph pattern. From this paper, it is expected that the results of the illustrative experiments, as well as the general issues presented in this study, will inspire further research. Some of the work in this paper is part of the Ph.D thesis of Pesigrihastamadya Normakristagaluh.